The comic to the classroom: A narrative didactic - Cabarcas Morales, Yoiseth Patricia (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2020)
This article presents a proposal that allows comics to be used as a didactic resource in classrooms. The study took as a starting point a specific question: How does the comic, as a didactic resource, allow the teaching of literature in the students of Basic Primary? To answer it, the methodology of the qualitative-interpretive paradigm was used, with a research-action design; the techniques and instruments used were participant observation, unstructured interviews, and the design of the teaching unit.